The age of surveillance capitalism : the fight for a human future at the new frontier of power - Zuboff, Shoshana, 1951- (PublicAffairs, 2019)
"Shoshana Zuboff, named "the true prophet of the information age" by the Financial Times, has always been ahead of her time. Her seminal book In the Age of the Smart Machine foresaw the consequences of a then-unfolding era of computer technology. Now, three decades later she asks why the once-celebrated miracle of digital is turning into a nightmare. Zuboff tackles the social, political, business, personal, and technological meaning of "surveillance capitalism" as an unprecedented new market form. It is not simply about tracking us and selling ads, it is the business model for an ominous new marketplace that aims at nothing less than predicting and modifying our everyday behavior--where we go, what we do, what we say, how we feel, who we're with. The consequences of surveillance capitalism for us as individuals and as a society vividly come to life in The Age of Surveillance Capitalism's pathbreaking analysis of power. The threat has shifted from a totalitarian "big brother" state to a universal global architecture of automatic sensors and smart capabilities: A "big other" that imposes a fundamentally new form of power and unprecedented concentrations of knowledge in private companies--free from democratic oversight and control"--